2015
DOI: 10.1302/0301-620x.97b11.35736
|View full text |Cite
|
Sign up to set email alerts
|

The rates of wear of X3 highly cross-linked polyethylene at five years when coupled with a 36 mm diameter ceramic femoral head in young patients

Abstract: Polyethylene wear debris can cause osteolysis and the failure of total hip arthroplasty. We present the five-year wear rates of a highly cross-linked polyethylene (X3) bearing surface when used in conjunction with a 36 mm ceramic femoral head. This was a prospective study of a cohort of 100 THAs in 93 patients. Pain and activity scores were measured pre- and post-operatively. Femoral head penetration was measured at two months, one year, two years and at five years using validated edge-detecting software (Poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…17 Selvarajah et al examined 36 mm ceramic heads against highly crosslinked polyethylene (Stryker X3) at 5 years follow-up and found a steady state wear rate of 0.110 mm/year using PolyWare. 18 For OxZr, our findings are consistent with the randomized controlled trial of Jonsson et al, who at 5 years follow-up found no difference (p = 0.6) in wear rates between OxZr (0.01 mm/year) and CoCr (0.02 mm/year) against highly crosslinked polyethylene (Smith & Nephew Reflection) using RSA. 19 They also reported no difference in HHS between groups.…”
Section: Discussionsupporting
confidence: 91%
“…17 Selvarajah et al examined 36 mm ceramic heads against highly crosslinked polyethylene (Stryker X3) at 5 years follow-up and found a steady state wear rate of 0.110 mm/year using PolyWare. 18 For OxZr, our findings are consistent with the randomized controlled trial of Jonsson et al, who at 5 years follow-up found no difference (p = 0.6) in wear rates between OxZr (0.01 mm/year) and CoCr (0.02 mm/year) against highly crosslinked polyethylene (Smith & Nephew Reflection) using RSA. 19 They also reported no difference in HHS between groups.…”
Section: Discussionsupporting
confidence: 91%
“…16 Although the rates were below the suggested osteolysis threshold, wear with 36 mm heads and partially irradiated polyethylene continues to be a concern, particularly with younger patients. 24 1 systematic review concluded that based on currently available literature, large diameter metal heads (>32 mm) or ceramic heads of any size are not proven to reduce femoral head penetration or osteolysis risk. 25 Allen et al 26 found no relationship between increased femoral head size and an increase in functional outcome at one-year follow-up, but did identify a trend toward reduction in dislocation rate with 36 mm heads.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year wear rates of sequentially annealed XLPE in conventional bearing THA has been reported at 0.11mm/year after bedding in. [17] The five-year linear head penetration rate observed in this series of dual mobility bearings is also approximately double (0.27mm/year).…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…However, the early penetration rates of dual mobility bearings at one-and two-years exceed fixed bearing traditional THA bearing XLPE penetration rates by essentially twice the amount, despite the older, less active patient population of this series. [17,18] Further, linear penetration rates did not correlate with age or activity level, but may be due to the smaller sample size and shorter term follow up.…”
Section: Accepted Manuscriptmentioning
confidence: 82%